Validation of the mathematical model of a solar panel using Matlab/Simulink tool - Vera-Dávila, Anderson Guillermo; Delgado-Ariza, Jhan Carlos; Sepúlveda-Mora, Sergio Basilio (Universidad Pedagógica y Tecnológica de Colombia, 2018)
The aim of this work is to perform a statistical analysis and validation of the results obtained from the simulations of a solar panel with Matlab / Simulink tool. To achieve this, a series of measurements of the power generated by the solar panel under different conditions of radiation and operating temperature were made. Later, the behaviour of the solar panel was simulated through the mathematical model and the model established by Simulink. Finally, an analysis of the approximation of each of the simulations with the real data was performed. The obtained results indicate that for the simulation by means of the mathematical model of the solar panel, a coefficient of determination of 0.9889 was obtained, whereas, for the model of the solar panel established by Simulink was 0.8673. The above shows the good correlation of each of the simulations performed with real values, reaching the conclusion that although the two methods used are close enough to reality, the mathematical model of the solar panel has a better approximation.